Noise exposure in the Malaysian living environment from a music education perspective - Chan, Cheong Jan (Universiti Pendidikan Sultan Idris, 2014)
The objective of this paper is to determine if the present state of noise exposure in the Malaysian living environment can be both a research and practical problem from the perspective of music education, by looking into the quality of the noise and its implications on the growth of a person. An impression of noise exposure level formed by using sound level meter reveals that social venues for Malaysians in their daily life could be noisier than industrial areas, many of which exceeded the recommended noise level set by the Department of Environment of Malaysia. An impression of the sound texture formed by analysing the recorded soundscape reveals a sharp contrast between the rural and urban areas in Malaysia in terms of quantities and varieties of sound source. Reflecting the findings of sound survey upon the Music Educationist’s Framework to Approach Noise/Sound in Living Environment, it is found that the noise exposure in the Malaysian living environment may pose threats to the quality of life of students, including their learning efficiency. Hence, it is a valid problem for music educationists to deal with both in their research and practical teaching.